The Other, the New, and the Old. Three Images of Leith in Irvine Welsh’s Porno - Zibalas, Deividas (Literatūra, 2021)
The present paper focuses on Irvine Welsh’s novel Porno (2002), the sequel to Trainspotting (1993). Most of the events of the novel take place in Edinburgh, and the changing face of Leith, a working-class neighbourhood, becomes the central axis in the story. By drawing on Edward Relph (1976) and Harold M. Proshansky et al. (2014 [1983]), this reading of Welsh’s novel attempts to show how the main characters self-consciously reflect on the neighbourhood’s changing identity, as well as the implications these changes have for their own sense of self. Multiperspectivity becomes the mode Welsh employs to project a nuanced image of Leith, as seen from the subjective perspectives of five internal narrators. What becomes of interest in the novel is not the identity of Leith per se, but the different images of Leith that emerge through the way the narrators identify with the neighbourhood. Specifically, three images of Leith are distinguished and explored in the paper.